(untitled) (Research, Society and Development, 2022)
Elimination of intraradicular infection is essential for the success of endodontic treatment. This study evaluated the antibacterial effects of nine different formulations of intracanal medication and irrigating solutions, based on calcium hydroxide (Ca(OH)2), calcium sulfate (CaSO4), and a chlorhexidine (CHX), against nine bacterial strains. Aerobic or facultative anaerobic bacteria were grown in trypticase-soy broth and the anaerobic strain was grown in pre-reduced anaerobically sterilized brain heart infusion. The evaluation was performed by using the agar diffusion test in aerobic and anaerobic conditions using plates containing mitis-salivarius agar or trypticase-soy agar. The results showed that practically all substances tested had some antibacterial activity, except for calcium hydroxide and calcium sulfate when associated only with glycerin, which did not show any bacterial growth inhibition. On average, the drugs that showed the greatest antibacterial effects were 2% chlorhexidine and calcium hydroxide paste in camphorated paramonochlorophenol (CPMC) /glycerin and 0.12% chlorhexidine. It was concluded that 0.12% CHX as intracanal medication based on 2% CHX gel showed better antimicrobial action of the substances tested on bacterial species of endodontic infection.